Pelatihan Perangkat Pembelajaran Abad 21 Berbasis Merdeka Belajar bagi Guru di Kabupaten Indragiri Hulu Riau - Supentri, Supentri; Arianto, Jumili; Ahmal, Ahmal; Yuliantoro, Yuliantoro; Separen, Separen (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to provide training on learning tools for teachers in Indragiri Hulu Regency, Riau. The service method used the form of discussions and practices, while the steps for implementing the service were; 1) the stage of preparation and development of training materials; 2) the training stage; 3) the stage of assistance in making learning devices. The results of this service indicated that the training could improve teachers’ ability to make learning tools, namely RPP, Media, Teaching Materials, LKPD, and Evaluation.